The British Constitution: A Very Short Introduction - Loughlin, Martin (New York Oxford University Press, 2013)
The British constitution has grown organically in response to changes in its economic, political, and social environment, and is not contained in a single authoritative text. In this Very Short Introduction, Martin Loughlin examines the nature and authority of the constitution, and its challenging prospects for the future.
Includes Index and Illustrations.
Keywords: Constitutional history -- Great Britai